THE ALLUREMENT OF COUNTERFEIT PURCHASE BEHAVIOR: A CASE STUDY AMONG YOUTH CONSUMERS OF MALAYSIA - Nurazreen Zulkeply; Azlia Jaapar; Noorsyahira Musa; Nur Hafizah Hidayat; Rosita Husain (International Journal of Accounting, Finance and Business, 2021)
Counterfeiting products are low-quality imitations of original products or fake luxury items. Producing and buying counterfeiting products are considered as the crime of the 21st century because its affect the luxury branded market. Lately, the rapid demand for these counterfeiting products caused the luxury branded market sufferer for losses, which strives for a low distribution to keep the demand high. Therefore, the purpose of this study is to determine the core factors on youth’s purchase behaviors towards counterfeit goods. The study also set out three common factors to examine the relationship of consumers’ buying behavior towards counterfeit products. The primary data were used, which was collected through questionnaires consisting of 27 questions. A survey of 200 respondents was conducted in Klang Valley. Correlation and regression analysis were used. The results of the study show that there is positive impact between past purchase experience on purchasing behavior of counterfeiting products. Thus, the experience of purchasing counterfeiting products is the core factors on purchasing of these products. By having a better understanding of the consumers’ purchasing behavior of buying counterfeit products of the genuine brand products can make better marketing strategies.